PV Microgeneration Perspective in Brazil: Approaching Interconnection Procedures and Equipment Certification - Alonso, A. M.S. [UNESP]; Marafao, F. P. [UNESP]; Goncalves, F. A.S. [UNESP]; Paredes, H. K.M. [UNESP]; Martins, A. C.G. [UNESP]; Brandao, D. I. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
Considering that distributed microgeneration systems are one of the most prominent trends in adding flexibility to the Brazilian energy matrix, regulation and certification standards become key players on providing well established interconnection procedures to the electrical power system, without degrading power quality and offering fair services to all institutions. Thus, this paper presents relevant information regarding to how the local interconnection procedures occur, as well as it presents different considerations on certification requirements for grid-tied inverters and PV modules available on the Brazilian market. Moreover, an overview of current constraints is raised, based on the comparison with other worldwide known standards and conditions for distributed energy systems.
Keywords: Brazilian DG rules; Distributed generation; Interconnection procedures; Microgeneration; PV equipment certification